Inhibition of miR-92a improves re-endothelialization and prevents neointima formation following vascular injury. (27th June 2014) - Daniel, Jan-Marcus; Penzkofer, Daniela; Teske, Rebecca; Dutzmann, Jochen; Koch, Alexander; Bielenberg, Wiebke; Bonauer, Angelika; Boon, Reinier A.; Fischer, Ariane; Bauersachs, Johann; van Rooij, Eva; Dimmeler, Stefanie; et al.
Abstract: Aims: MicroRNA (miR)-92a is an important regulator of endothelial proliferation and angiogenesis after ischaemia, but the effects of miR-92a on re-endothelialization and neointimal lesion formation after vascular injury remain elusive. We tested the effects of lowering miR-92a levels using specific locked nucleic acid (LNA)-based antimiRs as well as endothelial-specific knock out of miR-92a on re-endothelialization and neointimal formation after wire-induced injury of the femoral artery in mice. Methods and results: MiR-92a was significantly up-regulated in neointimal lesions following wire-induced injury. Pre-miR-92a overexpression resulted in repression of the direct miR-92a target genes integrin α5 and sirtuin1, and reduced eNOS expression in vitro . MiR-92a impaired proliferation and migration of endothelial cells but not smooth muscle cells. In vivo, systemic inhibition of miR-92a expression with LNA-modified antisense molecules resulted in a significant acceleration of re-endothelialization of the denuded vessel area. Genetic deletion of miR-92a in Tie2-expressing cells, representing mainly endothelial cells, enhanced re-endothelialization, whereas no phenotype was observed in mice lacking miR-92a expression in haematopoietic cells. The enhanced endothelial recovery was associated with reduced accumulation of leucocytes and inhibition of neointimal formation 21 days after injury and led to the de-repression of the miR-92a targets integrin α5 and sirtuin1. Conclusion: Our data indicate that inhibition of endothelial miR-92a attenuates neointimal lesion formation by accelerating re-endothelialization and thus represents a putative novel mechanism to enhance the functional recovery following vascular injury.